Low back disorders among athletes and its prevention - Kaneoka, K. (Sports injuries and prevention, 2015)
There are several pathomechanisms of lower back disorders among athletes such as lumbar intervertebral disc herniations, lumbar spondylolysis, facet joint disorders, sacroiliac joint disorders, muscle, fascia and its insertion disorders. In many cases except intervertebral disc herniations, there are less radiological findings so they should be diagnosed using functional classification. In order to decrease the mechanical stress to the pathological portion, it is thought to be important to maintain the proper spinal alignment (Neutral position) and the spinal segmental stability. The stabilization exercises which facilitates the deep trunk muscles (transversus abdominis, lumbar multifidus) function and the stretching for the muscles attached to the pelvis are recommended to achieve these tasks.